PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN POTENSI WISATA PANTAI DAN OPTIMALISASI PEMANFAATAN MEDIA SOSIAL DALAM PROMOSI POTENSI HASIL LAUT DESA KARAMA - Seppewali, Andi; Yanti, Reski Wahyu; Said, Supardi Muh; Adivar, Ahmad; Nengsi, Bella Alfia; Afiah, Syarifa Nurul (LPPM Universitas Bina Bangsa, 2024)
Karama Village located in Tinambung Subdistrict, Polewali Mandar Regency, West Sulawesi, has significant potential in marine products and tourism. However, this potential remains underutilized due to various challenges, including low human resource (HR) capacity in business management, limited use of social media for promotion, and a lack of environmental awareness. This community service program aims to enhance HR capacity and community creativity through business management training and social media optimization. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation).The stages include analyzing community needs, designing relevant programs, developing training materials and promotional content, implementing training activities, and conducting continuous evaluations. Results indicate significant improvements in business management skills, promotional effectiveness through social media, and sustainable management of local potential..These outcomes demonstrate that this community service program makes a tangible contribution to the sustainable economic development of Karama Village and can serve as a model for other rural areas in Indonesia.